2011
DOI: 10.1111/j.1439-0507.2010.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of topical OLEOZON® in patients suffering from onychomycosis

Abstract: The results of the use of ozonised sunflower oil (OLEOZON(®)) in the treatment of onychomycosis, based on its known antimycotic action and good skin tolerance, by means of a controlled randomised phase III assay are presented. A total of 400 outpatients were randomly divided into two groups: experimental, treated with topical OLEOZON(®), two times per day and control, treated also two times per day, with ketoconazole cream 2%, for 3 months. A patient was considered cured when the sick nails regained the normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 32 publications
0
36
0
3
Order By: Relevance
“…In fact, in some European countries, such as Germany, they can be obtained on prescription from pharmacies . Countries such as Cuba have developed commercial ozonated oils, and they have been successfully tested for the treatment of many diseases .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in some European countries, such as Germany, they can be obtained on prescription from pharmacies . Countries such as Cuba have developed commercial ozonated oils, and they have been successfully tested for the treatment of many diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Entre éstos, existen productos de origen natural que por su composición son mejor tolerados por el hospedero y muchas veces conllevan más de un benefi cio para los pacientes [9][10][11][12][13] . Entre los productos naturales con actividad antimicrobiana de uso tópico destacan el aceite derivado del árbol del té 28 , aceites esenciales y compuestos sulfhídricos de ajos 13 y de plantas silvestres como canela, sasafrás y bulbos [14][15][16][17][18] , así como el aceite de maravilla ozonizado [20][21][22][23]34,35 . Sin embargo, se requiere optimizar los productos naturales con el objetivo de avanzar hacia fármacos más activos, seguros y estables que permitan su proyección hacia el uso individual o combinado con moléculas tradicionales en el tratamiento de pacientes 9,11 .…”
Section: Discussionunclassified
“…Este producto se generó a través de un proceso original que implica la modifi cación del aceite, previo a la ozonización, lo que permite obtener un producto con elevada actividad antimicótica y baja viscosidad, facilitando su incorporación y mezcla con excipientes, así como su penetración en el tejido. Existe otro producto a base de aceite de maravilla ozonizado, denominado Oleozon®; sin embargo, este aceite es ozonizado directamente sin tratamiento previo 20,22,35 . Por difusión en agar se determinó que AMO 3 presentó actividad sobre todas las cepas de dermatofi tos evaluadas, contribuyendo a demostrar el amplio espectro de acción de este producto natural ozonizado [20][21][22][23][24]26 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A controlled randomized phase III trial using ozonized oil in patients suffering of onychomycosis demonstrated that this treatment is effective and even better than that of Ketoconazole and no side effects were observed (14).…”
mentioning
confidence: 99%